(untitled) (Interdisciplinary Studies Journal, 2024)
This article aims to present the possible conceptual contributions arising from the Projeto Burareiro de Educação Integral, a pedagogical experience implemented in the municipality of Ariquemes, state of Rondônia, between January 2005 and August 2006. Based on this, argue in favor of integral education, to the detriment of full-time, as the horizon of an educational policy, which meets those who desire alternative educational policies to the current hegemonic neoliberal conceptions. Both the pedagogical experience, carried out through a social laboratory, and the theoretical research, which preceded and followed it, were guided by epistemological principles of materialist dialectics and by the historical-critical method of academic production, whose analysis reached the possible contributions: introduction of the political dimension to the Marxian conception of education, new conception of interdisciplinarity and curricular integration, creation of the concepts of polytechnics as a pedagogical principle and integral polytechnic education. These contributions, together with the emergence of the concept of social sustainability, show that full-time policies, from 2010 onwards, are a political setback and an ideological shift towards neoliberalism.